B.03 Clinical utility of critical care EEG monitoring in a Canadian paediatric centre. (June 2019) - Din, F; Ganesan, S Lalgudi; Ochi, A; Otsubo, H; Go, C; Whitney, R; Chau, V; Cortez, M; Sharma, R; Hahn, CD
Abstract : Background: Continuous electroencephalographic (cEEG) monitoring is essential to diagnosing non-convulsive seizures (NCS), reported to occur in 7-46% of at-risk critically ill patients. However, cEEG is labour-intensive, and given scarcity of resources at most centres cEEG is feasible in only selected patients. We aim to evaluate the clinical utility of cEEG at our centre in order to optimize further cEEG allocation among critically ill patients. Methods: Using a clinical database, we identified critically ill children who underwent cEEG monitoring in 2016, 2017 and 2018. We abstracted underlying diagnoses, indication for cEEG monitoring, cEEG findings, and associated changes in management. Results: Over this three year period, 928 cEEGs were performed. Among the 100 studies analyzed to date, primary indications for monitoring were characterization of events of unclear etiology (32%), diagnosis of NCS (30%), and monitoring of therapy for seizures (17%). Seizures were captured in 31% of patients (22% subclinical only, 5% electroclinical only, 4% both), which resulted in a treatment change in 90% of cases. Non-epileptic events were captured in 26% of patients. Conclusions: cEEG yielded clinically meaningful information in 57% of cases, frequently resulting in management changes. Subgroup analyses by cEEG indication and ICU location will be presented.